Current evidence and future direction on evaluating the anticancer effects of curcumin, gingerols, and shogaols in cervical cancer: a systematic review - Rahim, Unwaniah Abdull; Mustapa, Marami; Mohamed Shakrin, Nik Noorul Shakira; Nurdin, Armania; Mohamad Taridi, Nursiati; Mohd Yusof, Yasmin Anum; Mad Nordin, Mariam Firdhaus; Che Roos, Nur Aishah (Public Library of Science, 2024)
Cervical cancer ranked fourth most common malignancy among women worldwide despite the establishment of vaccination programmes. This systematic review evaluates the anticancer properties of turmeric and ginger bioactive compounds, specifically curcumin, 6/10- gingerol, and 6/10-shogaol, and their combination in cervical cancer through in-vitro and invivo models. A comprehensive electronic search was performed using Science Direct, PubMed, and Scopus from inception until the second week of June 2024 for studies published in English. Only studies investigating the effects of curcumin, gingerol, shogaol, and/ or their combination in human cervical cancer cell lines and/or rodent animal models implanted with cervical cancer xenografts were included. Altogether, 27 studies were included in this review. The evidence gathered indicated that curcumin, 6/10-gingerol and 6- shogaol exert their anticancer action through modulation of cell signalling pathways, including AMPK, WNT, PI3K/AKT, and NF-κB pathway, and mediators including Bax/Bcl2, TNF- α, EGFR, COX-2, caspases-3, -9, p53, and pRb. However, the synergistic effect of these bioactive compounds is not known due to lack of evidence. In conclusion, curcumin, 6/10- gingerols, and 6-shogaols hold promise as therapeutic agents for cervical cancer. Yet, further research is essential to understand their combined efficacy, emphasising the need for additional studies exploring the synergistic anticancer effects of these bioactive compounds. Additional factors to explore include long-term effects and susceptibility of chemoresistant cervical cancer cells towards curcumin, shogaols, and gingerols. © 2024 Abdull Rahim et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.